La inteligencia interpersonal en el desarrollo del aprendizaje significativo en niñas y niños de 3 a 4 años en la unidad educativa 24 de mayo de la provincia chimborazo del cantón colta periodo 2023 - Ajitimbay Guamba, Erlinda Maribel (2023)
In this work, interpersonal intelligence was incorporated in the development of meaningful learning in children from 3 to 4 years old of the "24 de Mayo" Educational Unit of the Chimborazo Province of the Colta Canton, November 2022- March 2023, as a general objective. Methodologically, it was approached from a quantitative approach, with a cross-sectional descriptive study, non-experimental. The unit of study was 19 participants. The findings determined that teachers effectively develop activities that strengthen interpersonal intelligence, demonstrating a high percentage of management and transcendence in this area through meaningful learning. It was concluded that this topic is a contribution of great transcendence the application of pedagogical activities contributing to the evolution and growth of their emotional skills in the academic and integral aspect for children of 3 and 4 years of age